Semi-industrial drying of vegetables using an array of large solar air collectors - Condori, Miguel Angel (2017)
The design, structure, and evaluation of an indirect solar tunnel dryer are presented. This dryer corresponds to the air forced convection type. Two similar solar dryers were built and tested with vegetables on an industrial scale in Huacalera, northern Argentina, and operated by a cooperative of small agricultural producers. Each dryer consisted of a tunnel chamber of 450 kg load capacity and a bank of 10 solar collectors of 92 m2. The bank of large solar collectors allowed temperatures in the drying chamber above 50 °C for 6 h a day, mixing with ambient air to produce the correct temperature for drying vegetables. A maximum rank of outlet temperatures of 80–90 °C and temperature differences of 50–60 °C were obtained with minimum air flow of 0.06 kg/s and without load. The dryers were operated with different vegetables, obtaining e.g. dried slicing onion with final moisture content 0.09 in approximately 16 h of sun. The optimum point of the collector efficiency was determined with airflow of 0.4 kg/s, however, lower than 0.23 kg/s airflow is needed to obtain outlet temperatures above 50 °C. A financial evaluation of the dryer was also performed as a clean energy project, reflecting that the investment return rate of the device is 13 months. In this scenario NPV improves in a 438% compared with the conventional scenario and SNPV is suitable only in the case of solar dryer. Solar drying at semi-industrial scale is feasible with the proposed technology due to the gusts of wind and the day-night thermal amplitude of Huacalera.